Through Thick and Thin: How Fair Trade Consumers Have Reacted to the Global Economic Recession - Bondy, Tierney; Talwar, Vishal (2011)
Research on fair trade has flourished over the past decade as fair trade food products have gained popularity amongst consumers in many developed economies. This study examines the effects of recessionary economic conditions on fair trade consumers’ purchasing behaviour. An online survey was administered to 306 fair trade consumers from Canada, the United Kingdom and the United States of America. The results reveal a discrepancy among fair trade consumers as only consumers that purchase fair trade on an occasional basis adhered to established consumer behaviour norms, i.e. decreasing their purchases of fair trade products and becoming significantly more price aware. Respondents who actively consume fair trade generally remained loyal to their purchase. While some active consumers altered their purchasing behaviour, this phenomenon was not common amongst this group as no statistically significant changes were observed. Differences were also noted among the three countries as the Canadian and US fair trade consumers significantly decreased their consumption of fair trade as a result of the recession, whereas the UK consumers did not. In addition to the research results, theoretical and managerial implications will be discussed along with future research directions.
Keywords: United States of America; United Kingdom; Fair Trade; Economic Recession; cross-country analysis; Consumption; Canada; Consumer Behaviour